Mapping the "housing with care" concept with stakeholders: insights from a UK case study. Issue 4 (15th October 2018) - Wild, Annie; Clelland, David; Whitelaw, Sandy; Fraser, Sandy; Clark, David
Abstract : Purpose: The purpose of this paper is to present the findings of an early stage, exploratory case study of a proposed housing with care initiative (the Crichton Care Campus (CCC)). This sought the perspectives of a range of key stakeholders on the proposed model and how it might be best realised. The analyses of these findings show their relevance to debates on integrated housing with care, and reflect on the methodology used and its potential relevance to similar projects. Design/methodology/approach: The study used a transactive planning approach, where grounded views are sought from a variety of stakeholders. A purposive sample identified informants from relevant health, social care and housing organisations and nine semi-structured interviews were conducted. These were transcribed and data analysis was undertaken on an "interactive" basis, relating care theory to empirical expressions. Findings: The authors identify two contrasting orientations – inclusive "community-oriented" and professional "service-oriented". This distinction provides the basis for a rudimentary conceptual map which can continue to be used in the planning process. Two significant variables within the conceptual map were the extent to which CCC should be intergenerational and as such, the degree to which care should come from formalised and self-care/informal sources. The potential to achieve an integrated approach was high with stakeholders across all sectors fully supporting the CCC concept and agreeing on the need for it to have a mixed tenure basis and include a range of non-care amenities. Originality/value: This paper offers originality in two respects. Methodologically, it describes an attempt to undertake early stage care planning using a needs led transactive methodology. In more practical terms, it also offers an innovative environment for considering any approach to care planning that actively seeks integration – based on an acknowledgement of complexity, a variety of perspectives and possible conflicts. The authors propose that the concepts of "community-orientation" and "service-orientation" are used as a helpful basis for planning negotiations, making implicit divergences explicit and thus better delineated.